Tooth decalcification: A correlation between weight loss in a decalcified tooth with different decalcifying agents - Mohammad Imran Khan; Abhisheik Khare; Sameera Shamim khan; Anupama Mahendra; Abdullah Nasir; Arshad Khan (Elsevier, 2022)
The histopathological examination of mineralized tissues requires decalcification of teeth which is an essential and important step during tissue processing. In the present study we attempted to decalcify teeth using strong and weak acids and a chelating agent with various methods to identify completion of decalcification along with the observance of weight loss percentage of a tooth. Aim: To compare decalcification with conventional decalcification method with strong acid, weak acids and a chelating agent with respect to preservation of tissue structure, efficacy of staining in association with weight change. Materials and methods: A total of 64 multi-rooted and single rooted teeth were used, with group of 16 teeth, (16 molars, 16 pre-molars, 16 canines and 16 incisors) for each of the solution as Chelating agent (10% EDTA), Strong acid(10%HNO3), Weak acid (5% Tri Carboxylic acid) and Von Ebner's solution (hydrochloric acid & sodium chloride), were used in the study respectively. The efficacy of decalcifying agents was evaluated by recording the time taken by particular acid to decalcify the tooth completely and the weight change was observed at set intervals till the completion of decalcification. The endpoint of decalcification was also confirmed with radiographic and chemical methods. The decalcified teeth were then routinely processed, sectioned, and stained with haematoxylin and eosin stains. Different methods were used to confirm the completion of decalcification. After decalcification, all the teeth were examined macroscopically and microscopically. Results: At 70-80% of weight change of a tooth decalcification is complete. 10% EDTA was best suited to the soft and hard tissues in comparison to other solutions. 5% TCA was fair in staining quality and maintenance of hard tissue structures was satisfactory to 10%HNO3 and Von Ebner's solution. Conclusion: The final impression led to the proposition that EDTA was indeed the best decalcifying agent available if the results required are not urgent. For situations where time constraint is there, 5% Tri Carboxylic Acid can be used.